2004
DOI: 10.1002/app.20701
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐coated paper: Effects of nisin and different acids on the antimicrobial activity

Abstract: Chitosan coatings prominently improved both the gloss and oxygen barrier properties of paper. The gloss value in the machine direction was increased as a function of added chitosan. An oxygen-permeability value of 1.1 cm 3 /m 2 d was obtained when 6.9 g/m 2 chitosan was applied to 80 g/m 2 copy paper. In addition, the effects on the mechanical properties were positive, but not significant. The water-vapor permeability of the paper increased as a result of the chitosan coating. Chitosan dissolved in 1.6, 3.2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 40 publications
3
64
1
Order By: Relevance
“…The TS and %E of coated papers were greater than that of uncoated paper (23.94 ± 0.60 MPa; 4.52 ± 0.32%), which means that HPMC coating improved paper strength and ductility. Our results are in agreement with those of Vartiainen et al (2004), who reported that chitosan coating improved the tensile properties of paper and could be regarded as a reinforcement layer. The TS and %E values for HPMC-coated papers in this study are similar to those obtained by Rhim et al (2006) for alginate-or soy protein-coated paperboards.…”
Section: Tensile Propertiessupporting
confidence: 93%
“…The TS and %E of coated papers were greater than that of uncoated paper (23.94 ± 0.60 MPa; 4.52 ± 0.32%), which means that HPMC coating improved paper strength and ductility. Our results are in agreement with those of Vartiainen et al (2004), who reported that chitosan coating improved the tensile properties of paper and could be regarded as a reinforcement layer. The TS and %E values for HPMC-coated papers in this study are similar to those obtained by Rhim et al (2006) for alginate-or soy protein-coated paperboards.…”
Section: Tensile Propertiessupporting
confidence: 93%
“…[12][13][14][15][16][17] These reports, however, focus mainly on antimicrobial or medical applications, although barrier properties are also occasionally reported. Several, mostly Japanese, patents on chitosan-cellulose blends exist.…”
Section: Introductionmentioning
confidence: 99%
“…Freestanding films of chitosan exhibit very low oxygen permeability as was reported by Butler et al [65]. The possibility of obtaining an oxygen barrier by coating paper with chitosan has also been tested in an experiment in which a copy paper was coated with five layers using a bench-scale rod coater [60]. The total coat weight obtained was 6.9 g/m 2 and the oxygen permeability of this material was reported to be 1.1 (cm 3 mm)/(m 2 day kPa) when using a modified curtain coater on a bench scale.…”
Section: Chitosanmentioning
confidence: 82%
“…However, like other hydrophilic natural biopolymers, its properties as a packaging material also need to be improved. Chitosan exhibits high cohesive energy density due to its relatively high crystallinity and the hydrogen bonds between the molecular chains [57][58][59][60][61][62][63]. A study on composite films consisting of mixtures of chitosan and [52], 95% RH cellulose fibers showed that the films provided a good oxygen barrier [64].…”
Section: Chitosanmentioning
confidence: 99%